Characterization of a novel pharmacological Notch activator - Dey, Subhamita; Justus Liebig University Giessen (My University, 2023)
The Notch signalling cascade is evolutionary conserved across metazoan species. It exhibits pleiotropic actions during embryonic and post-natal development by governing a variety of cellular processes such as lineage commitment, maintenance of tissue stemness, proliferation and apoptosis. Pathway activation takes place by the establishment of an extracellular interaction between the Notch transmembrane receptor and its cognate ligand on two adjacent cells followed by sequential proteolytic processing of the Notch receptor itself. This results in the release and translocation of the Notch intracellular domain (NICD) to the nucleus. Interaction of NICD with the DNA binding protein and transcription factor RBPJ forms the molecular assembly resulting in the transcription of Notch target genes. In our cell-based screening to identify Notch boosters, LDC031192-treated cells show marked upregulation of Notch signatures. Activated or cleaved NOTCH1 and NOTCH3 receptor proteins, both, are significantly induced in LDC031192-induced cells. Pharmacological blockage of γαµµα-secretase-catalysed Notch processing abrogates LDC031192-mediated increase in NICD1 but not NICD3 indicating that transactivation is potentially NOTCH3-dependent. To test this hypothesis, NOTCH3 was genetically depleted and LDC031192 treatment in the NOTCH3-KO cells exhibit markedly reduced induction of the Notch target genes. Together, we identified a novel small molecule inducer that is Notch3-specific.
Keywords: ddc:570; ddc:610